Education During the Covid-19 Pandemic (Case Study: Nadiem Makarim's Leadership Style and Policies in Moving Education in Indonesia) - Fatonah, Fatonah; Ismail, Ismail; Darmansyah, Rafik; Yanfaunnas, Yanfaunnas (Proceeding International Conference on Malay Identity, 2023)
Much research has been done on the Covid-19 pandemic, both in terms of health, economy, and education. This study aims to examine the leadership style and policies of Nadiem Makarim in finding solutions to the pandemic that occurred in the field of education. This study uses a descriptive qualitative research method. The conclusion from this literature study is that the COVID-19 pandemic has changed the order of human life throughout the world, including Indonesia. Education is one sector that has an impact on this condition. The Minister of Education, Nadiem Makarim, with his young, energetic, innovative, and creative leadership style has changed the face of Indonesian education. From the results of the research conducted, there are several recommendations, namely: First, the government is expected to review the education system that has not been evenly distributed throughout Indonesia, how facilities and human resources are still far behind in the regions. Second, the public is expected to be more sensitive and concerned in technological developments so that technology can be used positively and beneficially and teaching staff are expected to learn technology and information so that they are not left behind on issues of knowledge development.